Broadband internet performance (QoS measurement) view from home access gateway in Malaysia / Mohamad Fazrino Mohd Idris - Mohd Idris, Mohamad Fazrino (2014)
The performance management is specified Quality of services (QoS) parameters is throughput, jitter, packet loss and delay. Network performance (NP) is very challenging to predict and guarantee in QoS performance because many service and applications rapidly increased. From that, Broadband wired assessment was conducted among 5 regions in Malaysia with 25 locations. Assessment is to benchmarking network and it is important to be used in operation and management of Network service providers (NSP) with MCMC requirement. The result of assessment was studied to find the best of benchmarking in a Network performance (NP). In addition from result, Internet Experience Measurement tool (IEMT) was developed also to more detail focusing a quality of experience (QoE) to cater user complaining slow browsing and slow connectivity.